Development of Critical Listening Teaching Modules Based on Gender Equality in the FETT of Muhammadiyah University Makassar - Hijrah, Hijrah; Hafid, Hilda (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This research aims to produce a Critical Listening teaching module based on gender equality that is valid and practical in the Critical Listening Teaching Course. This research product development procedure is based on the ADDIE model (Analyze, Design, Develop, Implement, Evaluation) and is limited to the third stage. This is due to the limitations of researchers. The first activity is the analysis process. This activity is carried out in two stages, namely problem analysis and needs analysis. Validation of teaching modules is carried out by listening subject experts and language experts. The practicality of the teaching module is seen through filling out a questionnaire for users of the teaching module, namely lecturers and students. The effectiveness of the teaching module is seen from the results of activities and student learning outcomes. The product was tested on students of the English Language Education Study Program. Based on the results of the student needs analysis, it was stated that students need learning resources that can support Critical Listening. However, this teaching module still requires further development because it is related to inserting material about gender equality in it.